2021
DOI: 10.29228/ehlj.52485
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Literacy on Obstetric Decisions of Women in Reproductive Age

Abstract: Aim In this study, it was aimed to investigate the effects of health literacy on obstetric decisions in women of reproductive age living in our region. Methods: This study was carried out on 400 registered women aged 15-49 who voluntarily participated in the survey in January 2018 -April 2018 period. In the survey, a questionnaire questioning the sociodemographic characteristics of the patients and a Turkish translated Health Literacy Survey-European Union (HLS-EU-47) questionnaire were used to measure the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Adequate HL increases participation in cancer screening ( 26 ). In a study questioning the relationship between HL and health screening in women, it was shown that improving HL should be an integral part of breast and cervical cancer screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate HL increases participation in cancer screening ( 26 ). In a study questioning the relationship between HL and health screening in women, it was shown that improving HL should be an integral part of breast and cervical cancer screening programs.…”
Section: Discussionmentioning
confidence: 99%